A case study in ethical failure: Twenty years of media coverage of Aboriginal deaths in custody - Wendy Bacon (Asia Pacific Network, 2005)
Australia’s media accountability systems (M*A*S) include the Australian Press Council, broadcasting self-regulatory schemes, public broadcasting charters, the Media, Arts and Entertainment Alliance (MEAA) Code of Ethics, journalism education and training programmes and organisations devoted to critiquing and enhancing the media. The explicit or implicit purpose of these systems is to enable the media to play its role in representative democracy, ensuring citizens can obtain information and communicate. So it is against these broader democratic goals that M*A*S and journalism itself must finally be evaluated. One way of doing this is to look at the end product—the media content produced by journalists—and examine how it reflects and responds to sources and events beyond the media itself. To explore further the implications of such an approach, in this article I have chosen a single case study—the Australian media’s coverage of Aboriginal deaths in custody over a 20-year period.